2022
DOI: 10.3390/vaccines10050767
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy among Behavioral Risk Takers

Abstract: The COVID-19 pandemic has emerged as a major public health issue, with vaccines serving as a vital preventive strategy to lower the global burden. Yet, despite national and local mandates, key sectors of the population continue to demonstrate lower compliance rates. In the United States, young adults have the lowest vaccination rates among the adult population. The goal of our study was to utilize the largest state-health survey to assess the key determinants of such hesitancy in order to create targeted inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…35,36 As a result of mass vaccination efforts by a range of public and private organizations, where health insurance information may not have been required, collected, or submitted, a substantial fraction of COVID-19 vaccine administrations were not recorded in insurance data. 37 Given the underrecording of COVID-19 vaccinations in insurance claims data, which leads to an underestimation of the true effect size, we empirically estimated the level of underrecording by calibrating against national and state vaccine registry data (eMethods 4 in the Supplement) and applied standard correction methods to all VE estimates. 38 Even if one would falsely assume no (0%) underrecording and completely disregard the necessary correction, the VE estimates would decline by about 10 percentage points, as illustrated in Table 2, eTable 5, and eTable 6 in the Supplement.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 As a result of mass vaccination efforts by a range of public and private organizations, where health insurance information may not have been required, collected, or submitted, a substantial fraction of COVID-19 vaccine administrations were not recorded in insurance data. 37 Given the underrecording of COVID-19 vaccinations in insurance claims data, which leads to an underestimation of the true effect size, we empirically estimated the level of underrecording by calibrating against national and state vaccine registry data (eMethods 4 in the Supplement) and applied standard correction methods to all VE estimates. 38 Even if one would falsely assume no (0%) underrecording and completely disregard the necessary correction, the VE estimates would decline by about 10 percentage points, as illustrated in Table 2, eTable 5, and eTable 6 in the Supplement.…”
Section: Discussionmentioning
confidence: 99%
“… 39 In the United States, Texas has banned healthcare worker mandates, however the state still has difficulty obtaining enough nurses to cover their patients. 40 Another study using data from the California Health Interview Survey evaluating COVID-19 vaccine hesitancy observed that initiatives such as mandates may not support vaccine uptake, citing that community level outreach should be prioritized, 41 a finding echoed by a further study finding that public health efforts to improve access to vaccines should be prioritized over mandates. 11 Similar to our findings, a survey study evaluating attitudes of healthcare workers in the UK reported that a large proportion of the sample favored education and building public trust over vaccine mandates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to implement practical, evidence based approaches to combat vaccine hesitancy among our students. More over, vaccine hesitancy represents a significant barrier to effectively managing and controlling the COVID-19 pandemic (Becerra & Becerra et al, 2022). A notion that has been confirmed by a computational based mathematical model that was performed by (Bartsch et al, 2020) and showed that the COVID-19 vaccine must have a coverage efficacy of at least 70% to effectively extinguish an ongoing pandemic by at least 80% without any other measures (Bartsch et al, 2020).…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%